The Government Responsibilities in Handling the Covid-19 Pandemic and Improving The Declining Economy in Indonesia - Tahegga Primananda Alfath; Tatiek Sri Djatmiati; Moh. Bagus; Adimas Ardhiyoko (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this research is to discuss health legal policy and the government responsibiliies in handling pandemic covid 19. Design/methodology/approach: The writing of this article is done in a normative juridical manner. The approach used is a conceptual and statutory approach. In analyzing the problem, it is done by interpreting the laws and regulations and relevant facts. Legal theories are used to analyze existing problems in handling COVID-19 and handling economic recovery. This writing is done by combining legal disciplines concerning administrative law, health law and economic law. Findings: Steps and legal policy have been taken to overcome the Covid-19 pandemic and improve the declining economy. This step requires a very large budget that is charged to the revenue and expenditure budget (APBN/APBD) and other posts that support the financing as regulated in Law No. 2 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Covid -19 Pandemic, and Presidential Regulation No. 99 of 2020 which has been amended by Presidential Decree No. 14 Year 2021. Research limitations/implications: Legally, the use of the budget for handling Covid-19 and maintaining economic stability, as well as policies carried out at the discretion that has been determined, must be accounted for by the authorities. In the study of Administrative Law, the responsible steps of the authorities are always accompanied by supervision and sanctions in the event of a violation. Originality/value: This paper is original Paper type: a Research Paper